The Safety and Efficacy of New DIVA Inactivated Vaccines Against Lumpy Skin Disease in Calves - Gaetano Federico Ronchi; Mariangela Iorio; Anna Serroni; Marco Caporale; Lilia Testa; Cristiano Palucci; Daniela Antonucci; Sara Capista; Sara Traini; Chiara Pinoni; Ivano Di Matteo; Caterina Laguardia; et al. (Vaccines)
Background: Lumpy skin disease virus (Poxviridae family—Capripoxvirus genus) is the aetiological agent of LSD, a disease primarily transmitted by hematophagous biting, affecting principally cattle. Currently, only live attenuated vaccines are commercially available, but their use is limited to endemic areas. There is a need for safer vaccines, especially in LSD-free countries. This research aims to develop and test a safe and efficacious inactivated vaccine. Moreover, in this study, we used keyhole limpet hemocyanin (KLH) as a positive marker to distinguish infected from vaccinated animals (DIVA). Methods: Lumpy skin disease virus was propagated on primary lamb testis cells and Madin–Darby bovine kidney cells (PLT and MDBK, respectively), and four inactivated vaccines were produced. The vaccines differed from each other with the addition or not of KLH and in cells used for virus propagation. To evaluate the safety and immunogenicity, the vaccines and two placebos were administered to six groups comprising six male calves each, and antibody response was investigated using both an enzyme-linked immunosorbent assay (ELISA) and a serum neutralization (SN) test. In addition, the LSD/γ-interferon test and KLH (IgM-IgG) ELISA were performed on the collected samples. Furthermore, the use of KLH allowed us to distinguish vaccinated animals in the ELISA results, without any interference on the strength of the immune response against the LSDV. Finally, the efficacy of one of four vaccines was investigated through a challenge, in which one group of vaccinated animals and one animal control group were infected with a live field strain of LSDV. Results: Four out of the six control animals showed severe clinical signs suggestive of LSD, and, therefore, were euthanized for overcoming the predetermined limit of clinical score. By contrast, the vaccinated animals showed only mild symptoms, suggesting a reduction in severe disease notwithstanding the incapability of the vaccine in reducing the virus shedding. Conclusion: The vaccines produced were safe and able to elicit both a humoral and a cellular immune response, characteristics that, together with the demonstrated efficacy, make our vaccine a good candidate for countering the LSD spread in disease-free countries, thus also facilitating disease containment throughout the application of a DIVA strategy.